Alia and the story of the rose: islam & me - Jafri, Adeeba (Goodword Books India, 2002)
"Alia and the Story of the Rose" follows a young girl named Alia who discovers a special rose with magical qualities. The story explores themes of beauty, kindness, and the importance of compassion. As Alia learns about the rose's significance, she also learns valuable life lessons about love, gratitude, and the interconnectedness of nature and humanity. The narrative encourages readers to appreciate the small wonders in life and the impact of their actions on the world around them.